The Political Economy of Robots
XXVI, 417 p. 11 illus., 8 illus. in color.
Keywords: This collection examines implications of technological automation to global prosperity and peace. Focusing on robots, information communication technologies, and other automation technologies, it offers brief interventions that assess how automation may alter extant political, social, and economic institutions, norms, and practices that comprise the global political economy. In doing so, this collection deals directly with such issues as automated production, trade, war, state sanctioned robot violence, financial speculation, transnational crime, and policy decision making. This interdisciplinary volume will appeal to students, scholars and practitioners grappling with political, economic, and social problems that arise from rapid technological change that automates the prospects for human prosperity and peace. Ryan Kiggins is Assistant Professor in the Department of Political Science at the University of Central Oklahoma, USA. He edited The Political Economy of Rare Earth Elements: Rising Powers and Technological Change, published as part of the International Political Economy series in 2015; and co-edited Toward an International Political Economy of Aritificial Intelligence: Prospects for Prosperity and Peace in the 21st Century, also part of the the International Political Economy series in 2021.p>.